Incorporation of Hepatitis C Virus E1 and E2 Glycoproteins: The Keystones on a Peculiar Virion - Vieyres, Gabrielle (MDPI, 2014)
Hepatitis C virus (HCV) encodes two envelope glycoproteins, E1 and E2. Their structure and mode of fusion remain unknown, and so does the virion architecture. The organization of the HCV envelope shell in particular is subject to discussion as it incorporates or associates with host-derived lipoproteins, to an extent that the biophysical properties of the virion resemble more very-low-density lipoproteins than of any virus known so far. The recent development of novel cell culture systems for HCV has provided new insights on the assembly of this atypical viral particle. Hence, the extensive E1E2 characterization accomplished for the last two decades in heterologous expression systems can now be brought into the context of a productive HCV infection. This review describes the biogenesis and maturation of HCV envelope glycoproteins, as well as the interplay between viral and host factors required for their incorporation in the viral envelope, in a way that allows efficient entry into target cells and evasion of the host immune response.